Energy losses in mechanically modified bacterial magnetosomes. (9th August 2016) - Molcan, Matus; Gojzewski, Hubert; Skumiel, Andrzej; Dutz, Silvio; Kovac, Jozef; Kubovcikova, Martina; Kopcansky, Peter; Vekas, Ladislau; Timko, Milan
Abstract: Magnetosomes are isolated from the Magnetospirillum magneticum strain AMB-1 bacteria. Two samples are compared: magnetosomes normally prepared of a 'standard' length and magnetosomes of a short length. Chains of magnetosomes are shortened by mechanical modification (cleavage) by means of sonication treatment. They represent a new geometry of magnetosomes that have not been investigated before. The effect of the sonication is analysed using transmission and electron microscopy, atomic force microscopy, and dynamic light scattering. Scanning imaging reveals three types of shortening effect in a sample of shortened magnetosomes, namely, membrane collapse, membrane destruction, and magnetosome cleavage. Dynamic light scattering shows a reduction of hydrodynamic diameter in a sample of shortened magnetosomes. The magnetic properties of magnetosomes are analysed and compared in DC and AC magnetic fields based on the evaluation of quasi-static hysteresis loops (energy losses) and calorimetric hyperthermia measurements (specific absorption rate), respectively. A sample of shortened magnetosomes behaves magnetically in a different manner, showing that both the energy loss and the specific absorption rate are reduced, and thereby indicates a variation in the heating process. The magnetic properties of magnetosomes, together with the new and stable geometry, are balanced, which opens the way for a better adaptation of the magnetic field parameters for particular applications.